The Impact Of Using Existential Therapy To Build Awareness Of Death For Victims Of Bullying - Hengki Yandri; Neviyarni Suhaili; Marjohan Marjohan; Ifdil Ifdil; Afdal Afdal (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2023)
Bullying is a very troubling phenomenon in society that occurs almost worldwide. Bullying has also penetrated the world of education, such as universities. This study aims to look at the impact of existential therapy in building awareness of death for bullies. The research method is experimental with a pretest and posttest design approach. The subjects of this study were active students in the odd semester of the 2021/2022 academic year at college X, and samples were taken with purposive sampling techniques totaling ten people. The data were revealed using a validated and tested bullying comprehension questionnaire. Descriptive data were processed using an interval formula to see the impact of existential therapy on building awareness of death for bullies who used Wilcoxon signed-rank tests. The results showed that the awareness of the death of bullies became better so that they no longer had the desire to commit bullying actions. The researchers are further expected to develop a group guidance model with an existential therapy approach to prevent bullying behavior in college students